Analisis Dampak Media Sosial terhadap Proses Pembinaan Hidup Rohani Mahasiswa Generasi Z - Utomo, Kurniawan Dwi Madyo; Meo, Yohanes Wilson B. Lena (Sekolah Tinggi Pastoral IPI Malang, 2025)
This study explores how social media affects the spiritual formation of Generation Z students in a major seminary. Generation Z has grown up entirely in an internet-saturated world where social media is central to daily life. For Catholic institutions seeking to nurture students’ spiritual growth, it is vital to understand how these platforms shape - and sometimes hinder - this process, as well as how students themselves perceive their influence. Data were collected through an online survey emailed to undergraduates, with 119 students completing the questionnaire, and through follow-up interviews with eleven participants. Quantitative data were analysed using linear regression to examine the relationship between social media use and spiritual well-being. The survey and interviews investigated students’ participation in spiritual practices - such as the Eucharist, personal prayer, and other devotions. Results show that social media has markedly reshaped the process of spiritual formation. Many students reported that frequent engagement with social media reduced their ability to be fully present in key spiritual disciplines, particularly during the Eucharist, in times of silent reflection, and in personal prayer.